Working memory‐related brain activity is associated with outcome of lifestyle intervention. (2nd July 2013) - Hege, M.A.; Stingl, K.T.; Ketterer, C.; Häring, H.U.; Heni, M.; Fritsche, A.; Preissl, H.
<x xml:space="preserve">Abstract</x> Objective Lifestyle interventions including reduction of caloric intake are still the most pursued option to treat obesity. However, their outcome in terms of weight loss strongly differs between participants. In our study, we hypothesized that initial differences in brain activation in a food specific memory task are associated with weight change during a lifestyle intervention. Design and Methods Magnetic brain activity was recorded during a one‐back visual memory task with food and nonfood pictures in 33 overweight and obese subjects before they underwent a lifestyle intervention. The intervention lasted 6 months and aimed for a reduction in daily caloric intake by 400 kcal. Body mass index (BMI) was determined before and after the intervention. Results Differences between outer tertiles representing people who increased their BMI by 1.4% ± 1.1% (non‐responders) and who reduced their BMI by −6.9% ± 2.6% (responders) are reported. Neuronal activity was related to BMI change in sensor and source space. Non‐responders showed higher activation in right inferior frontal and left occipital visual areas, whereas responders showed increased activation in right temporal areas including hippocampus and fusiform gyrus. Conclusions Differences in the cerebral response during a food specific memory task indicate an altered cognitive control over food intake. These differences might determine the ability to eat less and successfully lose weight.